Diversity of cetaceans in coastal seascape Golfo Dulce, Osa Peninsula, Costa Rica. - Oviedo, Lenin; Herra-Miranda, David A.; Pacheco-Polanco, Juan Diego; Figgener, Christine; Márquez-Artavia, Amaru; Quiros-Pereira, Wagner; Iñiguez, Miguel (Revista de Biología Tropical, 2015)
Golfo Dulce is a fiord-lilke embayment located in the southern Pacific of Costa Rica, this coastal-marine ecosystem harbors an important wealth in marine biodiversity, including cetaceans. In this study we describe the cetacean community of Golfo Dulce, in relation to the diversity of habitats constituting the seascape. Sighting data collected in periodic systematic surveys has yielded 943 records (2005-2014≈3 490h≈64 533km), of 12 species of cetaceans. A gradient of cetacean diversity is observed from the inner basin to the transitional-oceanic area at the entrance of the Gulf, with coastal bottlenose dolphin and spotted dolphin dominating the inner basin, and bottlenose dolphins and migratory humpback whales the sill area. Transitional oceanic habitat holds the greatest species diversity dominated by oceanic species, particularly piscivorous delphinids, including the off-shore form of bottlenose dolphins and the “Central American” spinner dolphin. We hypothesize the potential occurrence of a morphotype of pantropical spotted dolphins within Golfo Dulce, in contrast with S. attenuatta graffmani outside in open Pacific coastal waters. The pattern of cetacean community structure is established by the dynamic of area use by the species, which should be considered for the establishment of management and conservation strategies.